Analisis Perilaku dan Keputusan Konsumen Dalam Memilih Lembaga Pembiayaan untuk Kredit Konsumtif - Kasnaeny, Kasnaeny (Patria Artha University, 2017)
This study intends to examine the behavior that is behind the consumers decision, inchoosing a financing institution to perform consumer credit. In addition it aims todetermine the factors that influence consumers in deciding their choice in a non-bankfinancing institutions.This study used 125 respondents, determined based on Simple Random Sampling method.The research variable is taken based on the factors that become the attraction of nonbankfinancing company, as many as 22 variables. These variables were tested by theFactor Analysis method. Based on the result of the test on 22 variables, there are 4 corefactors that are: (1) the simple and speed factor of credit process, as the first factor of thegreatest influence, (2) location factor and physical attribute, as second factor, (3) ,ratefactor, and (4) employee service factor, as a fourth factor.The implications of the results of research on marketing strategy, namely: (1) Financingcompanies must be able to compete in various aspects and not only on price, becausefrom the results of research, consumers do not question the high price as long as there ismore value they get, both from service and from another aspect. (2) Consumers willchoose financing companies that fit their expectations, therefore managers of financecompanies should always find out what exactly consumers want, when consumers willbuy, how to buy, where they will buy. (3) Since a finance company is a service company,which essentially sells services (integible product), then the company manager mustmaximize services, ranging from quick procedures, office support, security, to servicesprovided by employees to consumers.